The Analysis Of Factors Associated With The Incidence Of Musculoskeletal Disorders (MSDs) In Batik Craftsmen - Budi Aswin; Fajrina Hidayati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Musculoskeletal complaints are complaints on the parts of the skeletal muscles that are experienced by a person with different levels ranging from very mild to very severe complaints. Musculoskeletal complaints cause pain, numbness, soreness, stiffness, tingling, swelling, tremors, sleep disturbances, as well as decreased work productivity and lost work time. This study aims to analyze the factors associated with the occurrence of musculoskeletal disorders in Batik Craftsmen. The population in this study were all 30 batik artisans in Danau Teluk District and were also used as research samples. Data will be analyzed using the chi-square test with (p = 0.05). The results showed that age (p=0.023), years of service (p=0.004), and work attitude (p=0.002) were significantly associated with complaints of musculoskeletal disorders (MSDs) in batik craftsmen. And there is no relationship between gender (p = 1.000) with complaints of musculoskeletal disorders (MSDs) in batik craftsmen. The conclusion in this study is that of the four variables studied, the variables associated with complaints of musculoskeletal disorders (MSDs) in batik craftsmen are age, years of service, and work attitude. Keywords: Musculoskeletal Disorders, Work Attitudes, RULA